Costing the Three Transformative Results - Fonds des Nations Unies pour la population (United Nations, 2020)
Costing the Three Transformative Results focuses on new research to estimate the costs associated the global effort led by UNFPA to: (a) end preventable maternal deaths, (b) end the unmet need for family planning, and (c) end gender-based violence and all harmful practices, including child marriage and female genital mutilation. This new analysis goes beyond calculating costs; it also identifies the specific interventions needed to achieve these three transformative results by 2030 – the deadline for achieving the Sustainable Development Goals – including developing country investment cases and costing of the work of UNFPA country programmes. This publication contains the methodologies and resulting cost estimates towards the achievement of each result.